2002
DOI: 10.1097/00000542-200210000-00034
|View full text |Cite
|
Sign up to set email alerts
|

PACU Bypass after Outpatient Knee Surgery Is Associated with Fewer Unplanned Hospital Admissions but More Phase II Nursing Interventions

Abstract: For outpatient lower extremity surgery, applying our PACU-bypass criteria led to an 87% PACU bypass rate with no reportable adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 5 publications
0
35
1
4
Order By: Relevance
“…27 Both Song and Williams et al have observed the phenomenon of an increased number of interventions in phase 2 recovery. 8,28 They have recognized that shortening phase 1 recovery time simply transfers the workload to phase 2 recovery; however, the extra interventions in the low-dose spinal group were not related to pain management or bladder management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Both Song and Williams et al have observed the phenomenon of an increased number of interventions in phase 2 recovery. 8,28 They have recognized that shortening phase 1 recovery time simply transfers the workload to phase 2 recovery; however, the extra interventions in the low-dose spinal group were not related to pain management or bladder management.…”
Section: Discussionmentioning
confidence: 99%
“…5 Several strategies involving regional anesthesia for joint arthroplasty have been designed to contain the cost of the surgery and secondary treatments and to decrease the economic burden on the health care system. [6][7][8] Williams et al showed that preoperative regional analgesia for orthopedic surgery was associated with a shorter anesthesia-controlled time and a lower sum of anesthesia-controlled time plus turnover time than general anesthesia performed in the operating room. 9 Such strategies have led to the design of new clinical pathways, which, along with the combination of different anesthetic techniques, have helped to shorten hospital stays for total knee arthroplasty and decrease costs.…”
Section: Résumémentioning
confidence: 99%
“…In patients undergoing lower limb orthopedic surgery, 87% (756/869) of patients were able to bypass the PACU, with no significant differences between mild and invasive surgical procedure categories. 11 The fast-tracked patients were also discharged home earlier, and had a lower incidence of unplanned hospital admission. However, they needed more nursing interventions in the ASU compared to patients who did not bypass the PACU.…”
Section: Fast-trackingmentioning
confidence: 99%
“…However, they needed more nursing interventions in the ASU compared to patients who did not bypass the PACU. 11 In another study of patients (aged 18-65 yr) undergoing knee arthroscopy and other simple ambulatory orthopedic procedures, 83% of 99 patients were successfully fast-tracked. The patients who achieved fast-track criteria did not increase operating room time, and were discharged home earlier.…”
Section: Fast-trackingmentioning
confidence: 99%
“…Among these techniques are local anesthetic wound infiltration 150,151 ; brachial, lumbar, and sacral plexus blocks; and nonepidural truncal blocks (paravertebral, transabdominal, and rectus sheath blocks). Peripheral analgesic techniques are important for facilitating cost savings in ambulatory surgery centers, especially when phase 1 recovery bypass is achieved 152,153 and unplanned admissions are reduced. 152,154 Peripheral regional analgesia delivered as a single injection or as a continuous infusion through a perineural catheter (PNC) provides analgesia superior to that with systemic opioids or epidural analgesia and is associated with minimal side effects, 110,154-158 better rehabilitation, 159,160 and shorter hospital stay.…”
Section: Peripheral or Perineural Analgesiamentioning
confidence: 99%